Surfing over masked distress: Internet addiction and psychological well-being among a population of medical students - Lateef Olutoyin Oluwole; Adetunji Obadeji; Mobolaji Usman Dada (Wolters Kluwer Medknow Publications, 2021)
Introduction: The Internet has become an integral part of our lives and tool for social interaction and communication and it is becoming worrisome; Internet use among students is assuming a dimension of profound preoccupation over other activities of daily living. Internet addiction (IA) may raise risk for sleep problem, and contribute to the development of some psychiatric disorders and worsening mental health. The aim of this study was to study the interrelationship between IA and psychological well-being of medical students. Methods: This cross-sectional study was carried out at the Ekiti State University College of Medicine among both preclinical and clinical medical students. The study population was the entire medical students. A total of 129 study participants (86 clinical and 43 preclinical students) were purposively enrolled, 83 males and 46 females. Data were collected from the students using a questionnaire that comprised four components: (i) Warwick-Edinburgh Mental Well-Being Scale, (ii) Young IA Test (YIAT), (iii) World Health Organization Alcohol Use Disorders Identification Test, and (iv) Insomnia Severity Index. Results: About half (51.9%) of the students who engaged the Internet dwelled on social media. Moreover, the least reason for using the Internet was for their academic assignments. Twenty-two (17.1%) of the participants scored below the minimum score for addiction on YIAT. This study revealed a statistically insignificant negative correlation between the pairs of IA score and mental well-being (r = −121, P = 0.198) and alcohol use and mental well-being (r = −0.10, P = 0.279). There existed a statistically significant positive correlation between IA and insomnia (r = 0.320, P = 0.000) and IA and alcohol use (r = 0.428, P = 0.000). There was an insignificant positive relationship between alcohol use and insomnia (r = 0.072, P = 0.414). Conclusion: IA and its associated problems among students would require earnest intervention to curb problematic use in order to attain good mental well-being.